2013
DOI: 10.1111/1751-7915.12040
|View full text |Cite
|
Sign up to set email alerts
|

Tight coupling of polymerization and depolymerization of polyhydroxyalkanoates ensures efficient management of carbon resources in Pseudomonas putida

Abstract: SummaryEnvironmental microbes oscillate between feast and famine and need to carefully manage utilization, storage and conversion of reserve products to exploitable sources of carbon and energy. Polyhydroxyalkanoates (PHAs) are storage polymers that serve bacteria as sources of food materials under physiological conditions of carbon demand. In order to obtain insights into the role of PHA depolymerase (PhaZ) and its relationship to a PHA polymerase (PhaC2) in the carbon management activity of Pseudomonas putid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 54 publications
5
21
0
Order By: Relevance
“…The essential role played by PhaC1 in PHA synthesis agrees with the data reported by Arias and colleagues () showing that maximal PHA accumulation correlates with a rapid and significant increase of phaC1 transcription. Sandoval and colleagues () reported that the expression of phaC1 in a mutant carrying a deletion of the whole cluster ( Pp UΔ pha ) was sufficient to restore PHA synthesis.…”
Section: Discussionsupporting
confidence: 91%
“…The essential role played by PhaC1 in PHA synthesis agrees with the data reported by Arias and colleagues () showing that maximal PHA accumulation correlates with a rapid and significant increase of phaC1 transcription. Sandoval and colleagues () reported that the expression of phaC1 in a mutant carrying a deletion of the whole cluster ( Pp UΔ pha ) was sufficient to restore PHA synthesis.…”
Section: Discussionsupporting
confidence: 91%
“…The peripheral supplier routes and regulatory networks ensure the funnelling of monomeric precursors towards the polymer. PHA synthesis and degradation are linked to the metabolic network thanks to a continuous cycle in which PHA synthase and depolymerase are simultaneously active, thus ensuring PHA turnover (Ren et al ., ; de Eugenio et al ., ; Arias et al ., ). Under PHA‐producing conditions, PhaZ KT depolymerase continuously releases 3‐hydroxy fatty acids from PHA granules.…”
Section: Metabolic and Regulatory Network Wiring The Pha Cycle A Crmentioning
confidence: 97%
“…In support of this view, the growth of P. extremaustralis under microaerobic conditions rescued the growth defect of the mutant strain unable to produce PHAs at low temperature (Tribelli and López, ). PHA metabolism is a dynamic process, with a continuous cycle of synthesis and degradation that helps adapt the carbon flow to the transient demand for metabolic intermediates (Escapa et al ., ; Arias et al ., ). Its importance would seem to be greater at low temperatures.…”
Section: Physiological Changes Associated With Growth At Low Temperatmentioning
confidence: 97%